ELES ERAM MUITOS CAVALOS: LEITURAS. BREVES CONSIDERAÇÕES ESTÉTICAS E POLÍTICAS - Silva, Fabiana Carneiro da (Revista Crioula, 2009)
THIS PAPER PROPOSES A REFLEXION ON HOW THE ROMANCE ELES ERAM MUITO CAVALOS (2001), BY LUIZ RUFFATO, DUE TO HIS AESTHETICAL PROCEDURES, BECOMES AN OBJECT TO VARIOUS CRITICAL READINGS. WE WILL DETAIN OURSELVES TO A COMPARATIVE ANALYSIS OF TWO ESSAYS ON THIS WORK, FOUND IN THE COMPILATION UMA CIDADE EM CAMADAS (2007). WE WILL ATTEMPT TO SITUATE THE WORK AND THE ESSAYS ON THEIR HISTORICAL CONTEXT AND EXPLICIT SOME OF THE POLITICAL IMPLICATIONS INHERENT TO THE CHOICE OF THE CRITERIA FOR THEIR AESTHETICAL VALUES.